Microbial Biomarkers in the Diagnosis of Diabetes: Current Approaches and Future Directions - Shahroz Ali (Pakistan Journal of Medicine and Dentistry, 2025)
Diabetes mellitus (DM) is a growing health concern across the globe, with its prevalence increasing by 1.6 to 3 times over the past three decades1. It ranks among the top 10 deadliest non-communicable diseases worldwide, leading to premature deaths and disability 2. Early diagnosis and prompt treatment are the only way to prevent disability and death. The human gut is colonized with different variety of bacteria, fungi, viruses, and eubacteria that play a vital role in digestion, immunity, and gut integrity. Gut dysbiosis refers to the alteration in the normal microbial composition of the gut. It has been found that dysbiosis is linked with metabolic syndrome and DM, supported by altered microbial abundance, shift in overall microbial composition, variety, and an increase F/B (Firmicutes/Bacteroidetes) ratio. This gut dysbiosis induces metabolic inflammation and disturbs glucose metabolism, contributing to the pathogenesis of DM. Some species are increased in DM, like Escherichia-Shigella, while beneficial species like Faecalibacterium prausnitzii are found to be decreased3.